Analysis of methods of protection from cyberthreats in IEEE 802.11 networks - Базилевич, Володимир Маркович (Ukrainian Information Security Research Journal, 2017)
The functioning of any modern enterprise is based on the use of information technologies, particularly, computer networks. Modern realities require design the networks with mobility and scalability. In order to effectively address these issues, it is advisable to use wireless IEEE 802.11 computer networks. At the same time, the use of wireless networks creates new challenges related to the development of a system of protection against cyber threats. This article analyzes and compares the methods used to create relevant systems, identifies the strengths and weaknesses of each of them, focusing on the programmatic aspect of protection as one that most often becomes the object of a cyberattack. The conducted analysis allows us to determine the expediency of using one or another method of protection or their combination, depending on the initial conditions, resources and goals that are put into the construction of the protection system.